Dental office management - Dietz, Ellen (Delmar, 1999)
This comprehensive book takes readers through the various tasks associated with front office dental procedures, preparing them for the office of the 21st century. Five Sections-the business of dentistry, practice communications, clinical records management, business and financial records management, and employment opportunities-are supported by learning objectives, key terms, and key concepts. Skill building for Success Student Activities (role-plays and problem-solving activities) and Skills Mastery Assessment Post-tests are provided at the end of each chapter